2020
DOI: 10.3390/insects11040209
|View full text |Cite
|
Sign up to set email alerts
|

Fungicides Reduce the Abundance of Yeast-like Symbionts and Survival of White-Backed Planthopper Sogatella furcifera (Homoptera: Delphacidae)

Abstract: The white-backed planthopper (WBPH) Sogatella furcifera is one of the most harmful pests of rice in Southeast Asia. The fat body of WBPH harbors intracellular yeast-like symbionts (YLS). YLS are vertically transmitted to WBPH offspring by transovarial infection. YLS play an important role in the WBPH life cycle. YLS diversity and function have been extensively studied in the brown planthopper (BPH) and small brown planthopper but not in WBPH, even though a novel strategy for controlling the BPH based on suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…aegypti adult mosquitoes, when the microbiota was modified to be enriched or exclusively composed by yeasts, individuals were found to maintain a high percentage of survival (68–100%) [ 108 , 116 ]. Similar results were observed for the adults of the planthopper species Sogatella furcifera [ 121 ] and N. lugens [ 122 ] since a fungicide treatment, which reduces YLS density in mycetocytes, decreases the insect survival by 60%. Yeasts can also have an impact on insect reproduction.…”
Section: Influence Of Yeasts On Insect Life-history Traits and Immune Systemsupporting
confidence: 79%
“…aegypti adult mosquitoes, when the microbiota was modified to be enriched or exclusively composed by yeasts, individuals were found to maintain a high percentage of survival (68–100%) [ 108 , 116 ]. Similar results were observed for the adults of the planthopper species Sogatella furcifera [ 121 ] and N. lugens [ 122 ] since a fungicide treatment, which reduces YLS density in mycetocytes, decreases the insect survival by 60%. Yeasts can also have an impact on insect reproduction.…”
Section: Influence Of Yeasts On Insect Life-history Traits and Immune Systemsupporting
confidence: 79%
“…Only 34% of nymphs reached adulthood under treatment with PC and 48% with P and PT. In the same way, studies with other delphacid species showed that a reduction of the number of YLS by the application of fungicides results in a lower survival (Pang et al., 2020; Shentu et al., 2016, 2019). In the present study, we also demonstrated that these three fungicides increased the nymphal development time compared to the negative control.…”
Section: Discussionmentioning
confidence: 89%
“…Considering planthopper's dependence on their YLS to complete their life cycle, these mutualistic symbiotes result ideal candidates to investigate the effects of their manipulation on the biological performance of these insects. One way to demonstrate the key role of YLS in vivo is reducing their abundance through the application of high temperatures (Noda & Saito, 1979;Zhang et al, 2008) or fungicides (Pang et al, 2020;Shentu et al, 2016Shentu et al, , 2019.…”
mentioning
confidence: 99%
“…The fungal symbionts, in particular, might represent a selective target to reduce the S. titanus presence in the European vineyards. Fungicides have proven effective under controlled conditions against the YLS species harbored by two planthoppers, Nilaparvata lugens (Shentu et al, 2016 ) and Sogatella furcifera (Pang et al, 2020 ), even if they are not environmental-friendly alternatives to insecticides. The Cardinium species, besides being known to negatively influence the reproduction of their hosts (Hunter et al, 2003 ; Weeks et al, 2007 ), might be also used for paratransgenesis approaches, namely as vehicles to specifically express foreign traits that may interfere with the phytoplasma acquisition/transmission or insect fitness.…”
Section: Discussionmentioning
confidence: 99%